The nationalism movement of Islam for independence of Patani Southern Thailand (1902-1945) - Jehma, Rosana; Sumardi, Sumardi; Sugiyanto, Sugiyanto (History Education, University of Jember, 2017)
The conflict in Patani is a contradiction between the Patani adn the kingdom of Siam, where’s society Patani feel the loss of political rights even remove their culture as the muslim. So it appers the national Islamic Patani. This study aims to learn about the Islamic nationalist movement in southern Thailand Pattani independence in 1902-1945. This study uses historical research, while the approach used is sociology political. The results showed that of various government policies thai want to escort and perpetuate the Patani region as the earth so that it conquered in 1902, a variety of reactions through the opposition in an effort to the pressure of the Kingdom of Siam. The implications of this research as a hope for other research or information considered to do the kind of research and development at the same time. Keywords: Islam nationalism, Independence of Patani.